HISTORICAL LITERATURE AS AN ENCULTURATION OF EDUCATION IN LOCAL WISDOM OF KINGDOM FAMILY IN JAVA - Muhammad Iqbal Birsyada; Darsono Darsono; Siswanta Siswanta; Sudartoyo Sudartoyo; Juang Kurniawan Syahruzah (UNIVERSITAS MUHAMMADIYAH METRO, 2018)
Historically historical literature has cultural roots especially in the development of the character of the values of local wisdom. In addition to the development of literary history culture can be one of the references in the process of writing historiography. This study aims to find the values of local wisdom in the work of historical literature. This research uses historical method. The conclusion in this study finds that the historical literature that developed in Java expressed the literary writer's poetry. Culturally, the contents of historical literature reflect the strategy of enculturation of the values of theroyal family's wisdom to the Javanese community. The suggestion in this study is to develop a further study of other forms of enculturation in historical literature in the development of local wisdom values of the Javanese community.